Degree of pain, most frequent musculoskeletal disorders and sociodemographic characteristics of patients treated at a physical therapy and rehabilitation center located in Villa El Salvador, Lima, Peru - Guevara Tirado, Alberto (2022)
Objective: To describe the socioeconomic characteristics of, the most frequent pathologies and symptoms of, and the subjective pain assessment by patients treated at a physical therapy and rehabilitation center located in the district of Villa El Salvador, Lima, Peru.Materials and methods: A descriptive, prospective and cross-sectional study conducted in 366 patients over 18 years of age, of both sexes, who attended their first physical therapy. Results: The patients reported moderate pain intensity in the pre-physical therapy and rehabilitation sessions assessment. Low back pain was the most frequent pathology, followed by neck pain and painful shoulder. Regarding the education level, most patients had secondary and technical education. Moreover, a statistical association was found between pain intensity and sex (p = 0.049), as well as between pain intensity and profession/occupation (p = 0.012).Conclusions: The patients who attended the physical therapy and rehabilitation service reported moderate pain before beginning their sessions. Based on the results of the socioeconomic characteristics, it is necessary to keep up preventive and promotional health measures to avoid possible risk factors that exacerbate musculoskeletal disorders which may interfere with patients’ future recovery and possible relapse.